Biometrics, physical characteristics and water absorption of Enterolobium maximum Ducke seeds - Farias, Carla Caroline Magalhães (2019)
Enterolobium maximum Ducke is a Fabaceae (Mimosoideae), arboreous, fast-growing, with excellent behavior for reforestation and restoration of degraded areas. The objective of this work was to study the biometry, water absorption and physiological quality of seeds of Enterolobium maximum. Length, width, thickness, mass, initial moisture, seed mass of 1000 seeds and number of seeds per kg were evaluated. The study of soaking was conducted with intact and scarified seeds, using three methods of soaking water (seeds submerged in distilled water), on paper and roll paper. The determination of the volume of seeds during imbibition was made using paper roll and three types of water: common (water supply), distilled and deionized water. The seeds exhibited homogeneity in physical features and biometrics, with an average of 19.0 mm, 11.5 mm wide, 6.43 mm thickness and 1.05 g of dough; There is great variation to the size and weight of seeds. Freshly harvested seed presents dormancy of seed coat impermeability imposed primary. The scarified seed and soaked by the method of paper roll present germination after 72 hours, characterized by the protrusion of the primary root and phase III identification of germination.